Performance of Ethiopian barley (Hordeum vulgare L.) genotypes under soil acidity stress and non‐stress conditions - Girma Abebe; Amsalu Nebiyu; Temesgen Menamo (Agrosystems, Geosciences & Environment)
Abstract Aluminum toxicity, a consequence of acidic soil conditions, is a major challenge for barley (Hordeum vulgare L.) growers in the Jima Zone of Ethiopia. This study aimed to evaluate tolerance and susceptibility of barley genotypes to soil acidity under field conditions. Note that 300 barley genotypes were used to evaluate under soil aluminum stress and non‐stress (lime) conditions in locations Jimma and Kafa in the 2022/2023 growing seasons. Significant genotype variations and interactions with management practices were observed for most traits, indicating considerable variability under stress and non‐stressed conditions. The average grain yield under non‐stress conditions was 3331.5 kg/ha, while it was 2778.4 kg/ha under stress, reflecting a yield reduction of 19.91%. High heritability (90% and 95.5%) and variation indicate a strong genetic influence on grain yield under non‐stressed and acidic soil conditions. A positive correlation of grain yield between stress and non‐stress (r = 0.824) indicates a high grain yield advantage for selecting individuals both under stress and non‐stress conditions. Additionally, among seven stress indices, stress tolerance index, aluminum adaptation index, geometric mean index, and mean productivity displayed strong positive correlations with grain yield under both stress and non‐stress conditions. Hence, based on these stress indices and grain yield, cluster analysis identified three distinct groups of 300 accessions. Cluster C‐I (13.66%) tolerant genotypes, Cluster C‐II (30.33%) intermediate genotypes, and Cluster C‐III (56%) stress‐susceptible genotypes. Barley genotypes that combine high yield and acid tolerance were identified, paving the way for further studies on adaptability and breeding line development, and advancing efforts to create improved barley varieties for the region.